KEKERASAN DALAM RUMAH TANGGA DALAM PERSPEKTIF SOSIOLOGI HUKUM - Rusli, Deni; Reza Umami; Ahmad Wahyudin (Bajang Institute, 2025)
Domestic violence is a complex and multidimensional social phenomenon. From a sociological perspective, this incident is not only viewed as a violation of the law, but also as a result of unequal power relations, patriarchal social constructions, and gender inequality within the family structure. This study uses a qualitative approach, examining the phenomenon of domestic violence through the theoretical framework of the sociology of law to understand the social factors underlying its occurrence. The results indicate that domestic violence is closely related to economic factors, low education, the social environment, and the weak position of women within the family. Although formal regulations such as Law No. 23 of 2004 concerning the Elimination of Domestic Violence have been enacted, their implementation still faces cultural and structural barriers. Therefore, a sociological approach to law emphasizes the importance of social transformation through education, women's empowerment, and changes in societal norms. The law must function not only as a repressive tool but also as a means to create social justice and protection for victims of violence, especially women.